Impacts of Financial Technology on Profitability: Empirical Evidence from Jordanian Commercial Banks - Alshehadeh A.R.; Elrefae G.A.; Khudari M.; Injadat E. (Springer Science and Business Media Deutschland GmbH, 2023)
This study aimed to illustrate the effects of the financial technology tools as a base for reinforcing financial inclusion indicators on profitability in the Jordanian commercial bank listed in the Amman stock exchange. A panel of data from 16 banks listed in the Amman stock exchange was used between 2010 and 2019. The financial technology changed the structure of the overall financial services, therefore, increase the availability for a wider social group. Further, the financial technology tools significantly reinforce the financial inclusion indicators over the studied profitability indicators, including return on assets and equity. It is recommended to adopt effective and modern financial, technological strategies that provide the marginalized social groups access to the financial services and products that meet their needs. Thus, getting the added value, which would increase the financial inclusion indicators. 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.